Lived Experiences among Rice Farmers on Tare Weight Deduction in Lapinig, Kapatagan, Lanao Del Norte - Arnel A. Esparcia; Zanlin Undona; Rubie Jane L. Laranjo; Shalley Mae D. Solatorio (Future Science / FSH-PH Publications, 2025)
This phenomenological qualitative study explored the lived experiences of 14 rice farmers in Lapinig, Kapatagan, Lanao del Norte, aiming to investigate the challenges and financial impact of unregulated 'Tarha' (tare weight deduction) practices on their livelihood. Using a phenomenological approach under qualitative research design and purposive sampling method, data were collected through in-depth interviews with 14 rice farmers. The data gathering was conducted over two (2) days. Thematic analysis revealed three key themes: (1) Excessive Tare Deduction as a Major Challenge, where farmers shared how large deductions significantly reduced their profit; (2) Coping Mechanisms through Sun-Drying and Palisan, reflecting how farmers reduce moisture and impurities to lower deductions; and (3) Calls for Reduction of Tare Deduction, where participants voiced the need for fairer and standardized deduction practices. Findings indicate that unregulated